2012
DOI: 10.1007/s10495-012-0698-1
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of apoptosis induction by 2-dodecylcyclobutanone, a radiolytic product of palmitic acid, in human lymphoma U937 cells

Abstract: The irradiation of fat-containing food forms 2-dodecylcyclobutanone (2-DCB) from palmitic acid (PA). In this study, we investigated whether 2-DCB and PA induce apoptosis in human lymphoma U937 cells. We found that cell viability decreased by 2-DCB and apoptosis was induced by 2-DCB and PA. 2-DCB and PA significantly enhanced the formation of intracellular reactive oxygen species (ROS). Apoptosis induced by 2-DCB and PA was strongly prevented by an antioxidant, N-acetyl-L: -cysteine. The treatment with 2-DCB an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The death receptor pathway triggered by stimulation of the death receptor CD95 (APO-1/Fas) results in receptor aggregation, and FADD and caspase-8 recruitment; subsequently, caspase-8 becomes activated and directly leads to a cascade that activates the apoptosis executor caspase-3 (36). The role of EGCG and a radiolytic product in triggering the Fas-caspase-8-medicated pathway in lymphoma U937 cells has been demonstrated by others (37,38). The enhanced expression of Fas mRNA and cleavage of caspase-8 with increasing EGCG concentrations observed in this study demonstrated that EGCG initiates the death receptor pathway to induce apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The death receptor pathway triggered by stimulation of the death receptor CD95 (APO-1/Fas) results in receptor aggregation, and FADD and caspase-8 recruitment; subsequently, caspase-8 becomes activated and directly leads to a cascade that activates the apoptosis executor caspase-3 (36). The role of EGCG and a radiolytic product in triggering the Fas-caspase-8-medicated pathway in lymphoma U937 cells has been demonstrated by others (37,38). The enhanced expression of Fas mRNA and cleavage of caspase-8 with increasing EGCG concentrations observed in this study demonstrated that EGCG initiates the death receptor pathway to induce apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Whether this phenomenon is idiosyncratic requires further studies in other cell lines. Previous studies have revealed the means by which EGCG or other natural agents cause the mitochondria to release cytochrome c : one direct means is mediated by Bcl-2 family proteins; the other is through Fas aggregated caspase-8, not directly activating the caspase-3 cascade but followed by cleaving of Bid to tBid and subsequent cytochrome c release that activates caspase-9 and caspase-3 (37,43). Although our results suggested that EGCG induces apoptosis through both the extrinsic (death receptor) and intrinsic (mitochondrial) pathways, it is unclear whether the two pathways are linked by Bid cleavage in Jeko-1 and Raji cells.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary horseradish peroxidase (HRP)-conjugated antibodies (1:5000) were purchased from Cell Signaling Technology. The band signals were visualized using a luminescent image analyzer (LAS4000, Fujifilm Co., Tokyo, Japan) with the ECL chemiluminescence system (Amersham Biosciences) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is well recognized that saturated fatty acids such as palmitic acid (C16:0) and stearic acid (C18:0) are cytotoxic to β-cells, and can induce apoptosis in vitro 22 , 23 . We found that 2-dDCB as well as its precursor to palmitic acid induced apoptosis in human lymphoma cells 24 . However, in vivo toxicity of dietary stearic acid has not been clearly demonstrated 25 , 26 , 27 .…”
Section: Discussionmentioning
confidence: 74%